VEGETATIVE PROVISION INDICATORS OF CARDIOVASCULAR SYSTEM AND PHYSICAL EFFICIENCY OF WOMEN ATHLET-SPRINTERS - M. V. Didenko; E. L. Mikhalyuk; S. N. Malakhova (Zaporožskij Medicinskij Žurnal)
In recent decades there has been a significant increase in physical activity during the preparation of qualified athletes-sprinters. However, it is clear that a simple increase in volume and intensity of training loads in preparation can not be infinite. Russian sport trainers see tactics mistakes. Some authors consider that optimum technique construction of training is possible when taking into account normalizing the volume and load intensity based on the types of circulation (TC).